Waterborne disease: an old foe re-emerging?. Issue 3 (2nd May 2005) - Smith, Daniel W; Belosevic, Miodrag; Neumann, Norman F
Abstract : In developed countries, clean and safe drinking water is taken for granted, and water treatment processes used to mass-produce drinking water have been hailed as one of the top five engineering achievements of the 20th century. However, in the last decade, several waterborne disease outbreaks have made us painfully aware of the personal, economical, societal, and public health costs associated with the impact of waterborne disease. There is evidence to suggest that the prevalence of waterborne disease may be dramatically underestimated in developed countries and that routine endemic exposure to waterborne pathogens may occur more frequently than originally perceived. A variety of demographical, societal, environmental, and physiological emergence factors likely play critical roles in enhancing the frequency of transmission of pathogens to hosts. This review focuses on the scope and impact of waterborne disease in developed countries and identifies issues surrounding the potential for rapid global emergence or re-emergence of waterborne disease. We examine relevant literature on Cryptosporidium parvum and Escherichia coli O157 as model organisms of study that support these concepts.